2010
DOI: 10.1016/j.foodres.2010.06.004
|View full text |Cite
|
Sign up to set email alerts
|

Dietary flaxseed supplementation improves endothelial function in the mesenteric arterial bed

Abstract: The aim of this study was to evaluate the influence of flaxseed diet supplementation on endothelial function in the mesenteric arterial bed of rats. Twenty-four rats were divided into 3 groups: Control Group (CG; 10% protein; 5% fiber; 7% lipid); Flaxseed Group (FG, supplemented with 25% flaxseed; 10% protein; 7% fiber; 11% lipid); and Modified Control Group (MCG; 10% protein; 7% fiber; 11% lipid). The blood was obtained by cardiac puncture (after 180 days) and the serum was separated for lipid profile analyse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 43 publications
1
10
0
Order By: Relevance
“…These results are in concordance with those reported by Brant et al (2012), who found flaxseed to prevent excess of body weight gain in pregnant rats because of its beneficial effects on lipids and glucose profiles. This same observation had also been made by Daleprane et al (2010) in weaned rats, for the reason that flaxseed fibres and long-chain N-3 polyunsaturated fatty acid content could reduce both appetite sensation and energy intake (Kristensen et al, 2013). According to Bielanski and Kowalska (2008), the addition of linseed oil to rabbit diets has a favourable effect on the composition of the lipid fraction of its meat, with a significant decrease in total saturated fatty acids and cholesterol, as well as an increase in polyunsaturated fatty acids contents.…”
Section: Body Weight and Clinical Observationssupporting
confidence: 81%
“…These results are in concordance with those reported by Brant et al (2012), who found flaxseed to prevent excess of body weight gain in pregnant rats because of its beneficial effects on lipids and glucose profiles. This same observation had also been made by Daleprane et al (2010) in weaned rats, for the reason that flaxseed fibres and long-chain N-3 polyunsaturated fatty acid content could reduce both appetite sensation and energy intake (Kristensen et al, 2013). According to Bielanski and Kowalska (2008), the addition of linseed oil to rabbit diets has a favourable effect on the composition of the lipid fraction of its meat, with a significant decrease in total saturated fatty acids and cholesterol, as well as an increase in polyunsaturated fatty acids contents.…”
Section: Body Weight and Clinical Observationssupporting
confidence: 81%
“…These results are satisfactory, since they show that weight loss did not affect the animals' GI from FC, which was similar to the CG. Daleprane et al 23 supplemented weaned rats with 25% of flaxseed up to 180 days old and found lower body weight in animals that consumed the oilseed, although the growth rate has been similar to the CG. Weight loss is recommended as a strategy to reduce the risk of cardiovascular disease 24 .…”
Section: Resultsmentioning
confidence: 99%
“…Although the present study has not assessed fatty acid composition in breast milk, we have observed that experimental diet contributes to higher body mass and pup length at weaning, because flaxseed is one of the richest plant ALA sources. [13][14][15] The experimental and control diets provided the same energy percentage from fat, which justifies the similar body and intra-abdominal fat mass in both groups. However, as reported by McCullough et al, 24 we observed that flaxseed intake significantly increased plasma and adipose ALA levels.…”
Section: Discussionmentioning
confidence: 99%
“…11,12 In previous experimental models, our group evidenced protective effects of diet containing 25 out of 100 g flaxseed flour on glycemia, cardiovascular risk and lipid profile reduction. [13][14][15] Nevertheless, little data are available on flaxseed flour effects on the relationship between adipose tissue and bone development during early life stages.…”
Section: Introductionmentioning
confidence: 99%